Analisis Hubungan Paparan Benzena dengan Faal Ginjal Pekerja Percetakan di Kota Surabaya - Yenitrisnawati; Noeroel Widjajati; Abdul Rohim Tualeka; Evi Setyawati (Media Gizi Kesmas, 2023)
Background: Benzene is a chemical whose exposure can cause occupational diseases arising from work activities, one of which can cause cancer. The sources of benzene in printing can come from ink cartridges, cylinders and in printers that are not closed. Objectives: This study aimed to analyze the relationship between benzene exposure and BUN and creatine levels of printing workers in Surabaya. Methods: This research is a descriptive observational study with a cross sectional design. The subjects of this study were 30 people who had met the criteria. The independent variables in this study were the levels of benzene in the air and the characteristics of workers, including age, years of service, and use of personal protective equipment (PPE). The dependent variable is BUN and creatinine as an indicator of kidney function. Results: The results showed that benzene concentration at six measurement points with the highest value was 15.64 ppm (already exceeding NAV). In the RQ calculation, there are 25 workers whose value is >1. The relationship between benzene concentrations with BUN and creatinine levels was in the unidirectional category and a strong correlation for BUN (r = 0.653) and sufficient for creatinine (r = 0.582), the relationship between age and BUN and creatinine levels was in the unidirectional relationship category and the correlation was very weak (r = 0.209 ; r = 0.140), the relationship between years of service with BUN and creatinine levels is in the unidirectional relationship category with sufficient correlation (r = 0.461; r = 0.322), while the relationship between PPE use with BUN and creatinine levels is in the unidirectional relationship category with correlation was moderate (r = 0.389) for BUN and very weak (r = 0.225) for creatinine. Conclusions: Based on the results, it can be concluded that there is a very strong relationship between the concentration of benzene and BUN and a strong relationship between the concentration of benzene and creatinine.